2020
DOI: 10.1021/acsomega.0c03974
|View full text |Cite
|
Sign up to set email alerts
|

Deep Insights into Heavy Oil Upgrading Using Supercritical Water by a Comprehensive Analysis of GC, GC–MS, NMR, and SEM–EDX with the Aid of EPR as a Complementary Technical Analysis

Abstract: Upgrading of heavy oil in supercritical water (SCW) was analyzed by a comprehensive analysis of GC, GC–MS, NMR, and SEM–EDX with the aid of electron paramagnetic resonance (EPR) as a complementary technical analysis. The significant changes in the physical properties and chemical compositions reveal the effectiveness of heavy oil upgrading by SCW. Especially, changes of intensities of conventional EPR signals from free radicals (FRs) and paramagnetic vanadyl complexes (VO2+) with SCW treatment were noticed, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 32 publications
(26 citation statements)
references
References 60 publications
(109 reference statements)
1
16
0
Order By: Relevance
“…It is also critical to understand how these changes correlate with petroleum bulk properties (i.e., viscosity and API gravity). Indeed, there have been several attempts to establish correlations between viscosity and compositional features of crude oils. , Nevertheless, the prediction of the viscosity of complex mixtures, such as extra-heavy oils and their blends with lighter solvents, as a function of molecular composition, has been regarded as a highly complex task. For instance, Sjöblom et al reported correlations between viscosity values and the concentrations of the main components (saturates, aromatics, resins, and asphaltenes, SARA fractions) for 200 crude oil samples from various regions of Russia and the Norwegian continental shelf.…”
Section: Introductionmentioning
confidence: 99%
“…It is also critical to understand how these changes correlate with petroleum bulk properties (i.e., viscosity and API gravity). Indeed, there have been several attempts to establish correlations between viscosity and compositional features of crude oils. , Nevertheless, the prediction of the viscosity of complex mixtures, such as extra-heavy oils and their blends with lighter solvents, as a function of molecular composition, has been regarded as a highly complex task. For instance, Sjöblom et al reported correlations between viscosity values and the concentrations of the main components (saturates, aromatics, resins, and asphaltenes, SARA fractions) for 200 crude oil samples from various regions of Russia and the Norwegian continental shelf.…”
Section: Introductionmentioning
confidence: 99%
“…Asphaltenes from Ashalchinskoe oil deposits (Russia) were separated from the crude oil by precipitation with heptane (40:1) for 24 h and subsequent purification from maltenes (saturate, aromatic, and resin) in a Soxhlet extractor. Various rheological and analytical data of the original crude oil, extracted asphaltenes, and other oil fractions are given in refs and .…”
Section: Methodsmentioning
confidence: 99%
“…The disruption of n-alkanes in saturated hydrocarbons of heavy crude oil before and after upgrading was investigated using an Agilent 7890A gas chromatography. The description of the analysis methodology is described in detail in our previous work (Djimasbe et al 2020).…”
Section: Gas Chromatography Analysismentioning
confidence: 99%